The Role of Media "X" in Shaping Public Space in the 2024 Election - Hidayatullah, Syarif; Aleksa, Nur Eka; Azzahra, Vendya Shifa; Fitah, Shabrina Nawal; Nisa, Pia Khoirotun (Journal of Social Science and Education Research, 2025)
This article discusses the role of social media application "X" in shaping public spaces during the 2024 elections in Indonesia. This research shows that social media has become an important tool for politicians to convey campaign messages, respond to issues, and interact with voters effectively. While social media offers advantages in increasing political participation, there are also challenges such as polarization and the spread of misinformation. The "X" app serves as a platform that allows for the rapid dissemination of information, creating a space for various political actors to communicate and shape public opinion. Through a qualitative approach, this study analyzes how the "X" application facilitates political discussion and its impact on public participation and the quality of democracy. The results of the study show that social media can strengthen public space, although it also has the potential to cause conflicts and the spread of hoaxes. As such, it is important to understand the dynamics of interaction on social media and how it affects people's perception of the political process. This research is expected to provide useful insights for better use of social media in the political context in the future.